G63(P) Investigation of Familial Vesico-Ureteric Reflux in Infants, is It Worthwhile?. (4th June 2013) - Hubbard, R; Collins, N; Matthew, D; Baines, L; Lambert, H
Abstract : Aims: Vesico-ureteric reflux (VUR) is known to be familial and inherited, but screening of asymptomatic individuals is controversial. In our centre families with an index case with proven VUR or evidence of reflux nephropathy (RN) on imaging, are counselled about the hereditary nature and given information about possible clinical problems associated with VUR. They are offered screening of newborn and infant first-degree relatives by contrast micturating cystourethrogram (MCUG). The aim of this audit was to look at the outcome of screening infants by contrast MCUG from data collected over 10 years from one hospital. Methods: The reports of all MCUGs on under one year olds performed during the last 10 years were reviewed. All MCUGs had been reported or verified by a consultant radiologist. We obtained information from reports and electronic letters and used these to ascertain those MCUGs done for screening purposes; obtain results; and determine clinical outcomes where possible. Results: 203 MCUGs out of a total 1738 were done for the investigation of familial VUR or reflux nephropathy. A further 2 were requested but not done. 39 cases with VUR were found. We had discharged 5 children (13%); in 4 of these VUR has been demonstrated to have resolved; and 34 (87%) are currently being followed up. Of these, 2 have scarring with recurrent UTIs and 1 has a scarred kidney but VUR has resolved. Conclusion: 19% of asymptomatic infants screened for VUR because of a positive family history of VUR or RN have themselves got VUR, with the majority (67%) having bilateral VUR. By identifying these cases resources and education are targeted to those families to encourage rapid diagnosis and treatment of UTIs with the ultimate aim of preventing scarring.